PENGARUH FRAUD PENTAGON TERHADAP FRAUDULENT FINANCIAL REPORTING - Marsheilla Aisyah Rezianti; Sri Wibawani Astuti; Agung Prasetyo Nugroho Wicaksono (Program Studi Akuntansi FPEB UPI, 2022)
This study is a quantitative study that aims to analyze the effect of the fraud pentagon on fraudulent financial reporting. Pentagon fraud is measured by financial target (ROA), financial stability (ACHANGE), external pressure (LEV), financial need (OSHIP) as a proxy for pressure. Nature of industry (RECEIVABLE) and ineffective monitoring (BDOUT) as proxies for opportunity. Change in auditor as a proxy for rationalization. Change in director (Variable Dummy) as a proxy for competence (ability). Duality of CEO (Variable Dummy) and frequent number of CEO picture (CEOPIC) as proxies for arrogance and fraudulent financial reporting are measured by the M-Beneish Score and Dummy based on the results of the M-Beneish Score. The sampling method is a purposive sample consisting of 132 companies from 180 manufacturing companies in 2018-2019. Data analysis method using Partial Least Square (PLS). This study uses a significance level of 0.1. The results of this study indicate that only the opportunity variable has a positive effect on fraudulent financial reporting. Meanwhile, the variables of pressure, rationalization, competence, and arrogance have no effect on fraudulent financial reporting.Keywords: pressure; opportunity; rationalization; competence; arrogance